From blueprint to practice: an innovative dynamic 9-box grid improves exercise participation and aerobic capacity in graduate students - Chen, Lei; Li, Aichun; Chen, Wenhao; Wang, Hongzhuang; Zhou, Junlai; Sun, Mingyun (Frontiers in Public Health, 2025)
BackgroundGraduate students face considerable health risks due to sedentary behavior and academic stress, often demonstrating a marked intention–behavior gap in physical activity (PA). This study developed a two-dimensional 9-box grid model based on total exercise volume (TEV) and aerobic capacity (AC) to compare the efficacy of weekly versus monthly feedback in improving AC and PA participation among graduate students.MethodsA quasi-experimental trial was conducted over eight weeks. Thirty-two graduate students, stratified by baseline AC evaluated in a 12-minute run test, were randomized into two arms, weekly feedback (n = 16) and monthly feedback (n = 16). Feedback was delivered through a dynamic 9-box grid that integrated weekly TEV on the x-axis and periodic AC on the y-axis. The primary outcomes were changes in the 12-minute run performance and TEV. Secondary outcomes included scores from the Exercise Identity Scale (EIS) and the Self-Efficacy for Exercise Scale (SEE-C). Thirty graduate students (n = 15 per group) completed the trial and were included in the final analysis.ResultsSignificant group × time interactions were observed for 12-min run distance (F = 4.29, p = 0.024, η2 = 0.241) and score (F = 6.49, p = 0.005, η2 = 0.325). The weekly feedback group demonstrated sustained improvements across all intervals (p < 0.001, Hedges’ g = 1.16–1.78), while the monthly group improved only post-intervention. Weekly feedback also resulted in significantly greater gains in self-efficacy (p = 0.044, g = 0.77) and higher TEV scores at multiple timepoints (p < 0.05). Both groups showed improved exercise identity (p < 0.001), with no between-group difference. Center of gravity analysis indicated greater migration toward healthier grid zones in the weekly group (ΔG = −1.93 vs. −1.47).ConclusionThe dynamic 9-box grid model effectively enhances aerobic capacity, promotes physical activity, and strengthens psychological outcomes through dual-axis evaluation and closed-loop feedback. Weekly feedback demonstrates superior efficacy in sustaining behavior modification and facilitating tier progression. This model provides a replicable, theory-informed strategy for health behavior management in graduate student populations.